Influence of calcium dose and time of application on tuber yield and processing quality of potato (Solanum tuberosum) - Kumar, Parveen; Rawal, Sanjay; Kumar, Dinesh; Kumar, Rajeev; Saini, Neeraj; Chand, Ramesh; Sandhu, K. S. (Annals of Agricultural Research, 2016)
A field experiment was conducted during 2008-2010 at CPRI Campus, Modipuram, Meerut to study the effect of calcium on quality and productivity of three potato varieties. Results indicated that cvs Kufri Bahar and Kufri Sindhuri recorded 12% improvement in the marketable tuber yields with 200 kg Ca/ha in two splits. Processing cv. Kufri Chipsona- 3, also tended to improve processing grade yield with this treatment without showing any statistical significance. All the three cultivars observed significant enhancement of specific gravity with moderate calcium application. Chip colour score of processing cv. Kufri Chipsona- 3 improved distinctly with moderate Ca level of 100 kg Ca/ha (2.16) over control (2.70) at harvest time. Glucose content in Kufri Chipsona- 3 also exhibited similar trend consistently as it declined with Ca nutrition. No internal and external defects were observed in any treatment under study during both the years. Moderate calcium application (200 kg/ha) in two equal splits i.e. at planting and 20-25 days after planting during earthing operation as gypsum may be advised to potato growers for mitigating abiotic stress of higher temperatures under field conditions to attain better tuber productivity and post harvest quality.